ANALISIS PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT DI SDN 8 NUSA KENYIKAP - Suyatmin; Kurnia Dyah Anggorowati; Beti Febriani (STKIP Melawi, 2026)
Abstract: The study aims to analyze the implementation of Clean and Healthy Living Behavior (PHBS) at SDN 8 Nusa Kenyikap. This research employed a qualitative research method with a case study approach. The research subjects were the principal, the Grade VI homeroom teacher, and 16 Grade VI students. The object of the study was the analysis of the implementation of clean and healthy living behavior. The research procedures consisted of the preparation stage, implementation stage, and final stage. Data collection techniques included questionnaires, interviews, and documentation. The research instruments were questionnaire sheets, interview guidelines, and documentation. Data analysis techniques involved data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The results of the PHBS questionnaire were categorized as moderate, with an average percentage of 76%. The interview results with the principal and the Grade VI homeroom teacher indicated that the school had made efforts to educate and habituate PHBS involving the entire school community, which was strengthened by documentary evidence. In conclusion, the PHBS indicators at the school have been implemented but still require improvement to achieve good or very good categories. Keywords: Implementation, Clean and Healthy Lifestyle Behavior Abstrak: Penelitian bertujuan menganalisis Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) di SDN 8 Nusa Kenyikap. Metode penelitian menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Subjek penelitian adalah kepala sekolah, wali kelas VI, dan siswa kelas VI berjumlah 16 siswa. Objek penelitian adalah analisis penerapan perilaku hidup bersih dan sehat. Prosedur penelitian adalah tahap persiapan, tahap pelaksanaan dan tahap akhir. Teknik pengumpulan data menggunakan kuesioner, wawancara, dan dokumentasi. Instrumen penelitian menggunakan lembar kuesioner, wawancara, dan dokumentasi. Teknik analisis data yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Pengecekan keabsahan data menggunakan triangulasi sumber dan triangulasi teknik. Hasil kuesioner PHBS tergolong sedang dengan rata – rata presentase 76%, Hasil wawancara kepala sekolah dan wali kelas VI menunjukkan pihak sekolah telah melakukan upaya edukasi dan pembiasaan PHBS yang melibatkan warga sekolah, diperkuat dengan bukti dokumentasi. Kesimpulannya, indikator PHBS di sekolah telah diterapkan dan perlu peningkatan supaya mencapai kategori baik atau sangat baik. Kata Kunci : Penerapan, Perilaku Hidup Bersih dan Sehat